Protesi di rivestimento e stemless in chirurgia della spalla. Indicazioni, limiti e prospettive - Bove, A.; Cozzolino, A.; Soldati, A.; Matino, G.; Del Regno, N. (Lo Scalpello - Journal, 2019)
RESURFACING AND STEMLESS ARTHROPLASTY IN SHOULDER SURGERY. INDICATIONS, LIMITS AND PERSPECTIVES Small implants in shoulder replacement surgery represent a viable alternative to traditional surgery in specific conditions. Resurfacing and stemless implants have been introduced with the goal of preserving bone, reduce the risk of humeral periprosthetic fractures and simplify revision procedures. Clinical studies show very good clinical results and low complication rates in selected patients when correctly implanted. The use of small implants in shoulder replacement surgery appears to be a viable option for shoulder replacement, especially in young patients, even though future studies are required to assess the long-term outcomes.